Diseño e implementación de un pantógrafo mediante control numérico computarizado - CNC para realizar procesos de fresado en madera en el laboratorio de ingeniería electromecánica de la Universidad Técnica de Cotopaxi en el periodo 2015 - Gutiérrez Cevallos, Marco Bladimir (2015)
Today global industries are characterized by making high quality products which has led to extreme competition among large companies, which has also affected smaller producers because they do not possess the technology to be level large industries the same as getting constantly renewed high-tech machine tools and design software according to the decade in which they are located. Among the technological advances that are currently on the market are the numerical control system computerized that it allows different industrial jobs difficult to execute by the human personnel, allowing the optimization of time and money. Considering the Province of Cotopaxi, Latacunga Canton can be seen a technological breakthrough and increased industrial production, however, it is visible that there are small producers who can not acquire machinery to be at the same level as the highly industrialized companies....